Identification of the corn pathogen pantoea stewartii by mass spectrometry of whole-cell extracts and its detection with novel PCR primers - Wensing, Annette; Zimmermann, Stefan; Geider, Klaus (Applied and environmental microbiology, 2010)
Pantoea stewartii subsp. stewartii is the causative agent of Stewart's wilt, a bacterial disease transmitted by the corn flea beetle mainly to sweet corn (Zea mays). In many countries, it is classified as a quarantine organism and must be differentiated from other yellow enteric bacteria frequently occurring with corn. We have created novel primers from the pstS-glmS region of P. stewartii for use in conventional PCR (cPCR) and quantitative PCR (qPCR). To facilitate rapid diagnosis, we applied matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS) analysis. Using whole-cell protein extracts, profiles were generated with a Bruker microflex machine, and the bacteria classified. P. stewartii strains were clearly distinguished from strains of Pantoea agglomerans, Pantoea dispersa, and Pantoea ananatis. Dendrogram analysis of the protein profiles confirmed the score values and showed the formation of separate clades for each species. The identification achieved by MALDI-TOF MS analysis agrees with the diagnosis by specific PCR primers. The combination of both methods allows a rapid and simple identification of the corn pathogen. P. stewartii subsp. stewartii and P. stewartii subsp. indologenes are highly related and can be distinguished not only by virulence assays and indole tests but also by a characteristic pattern in the nucleotide sequence of recA.